Proceedings of the 29th Annual Conference on Computer Graphics and Interactive Techniques 2002
DOI: 10.1145/566570.566612
|View full text |Cite
|
Sign up to set email alerts
|

Precomputed radiance transfer for real-time rendering in dynamic, low-frequency lighting environments

Abstract: We present a new, real-time method for rendering diffuse and glossy objects in low-frequency lighting environments that captures soft shadows, interreflections, and caustics. As a preprocess, a novel global transport simulator creates functions over the object's surface representing transfer of arbitrary, low-frequency incident lighting into transferred radiance which includes global effects like shadows and interreflections from the object onto itself. At run-time, these transfer functions are applied to actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
575
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 589 publications
(580 citation statements)
references
References 51 publications
0
575
0
5
Order By: Relevance
“…The result of the rotation will be a full set of spherical harmonic coefficients, representing the Phong lobe in global space, ready to use for computation of (5). For lowfrequency glossy transfer, a 25 coefficient (degree 4) spherical harmonic approximation to the glossy transfer function yields satisfying results [Sloan et al 2002], and for the purposes here, a 25 coefficient approximation to a Phong model of low shininess (s ≤ 6) is used.…”
Section: Rendering Using a 3d Spherical Harmonic Gridmentioning
confidence: 99%
See 2 more Smart Citations
“…The result of the rotation will be a full set of spherical harmonic coefficients, representing the Phong lobe in global space, ready to use for computation of (5). For lowfrequency glossy transfer, a 25 coefficient (degree 4) spherical harmonic approximation to the glossy transfer function yields satisfying results [Sloan et al 2002], and for the purposes here, a 25 coefficient approximation to a Phong model of low shininess (s ≤ 6) is used.…”
Section: Rendering Using a 3d Spherical Harmonic Gridmentioning
confidence: 99%
“…They showed that diffuse transfer could be accurately simulated by representing the environment illumination with a nine component spherical harmonic. Sloan et al [2002] later extended the use of spherical harmonics for Precomputed Radiance Transfer (PRT) of glossy materials, performing expensive computations as a precomputation step.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…First, many fast techniques for acquiring the light transport of real scenes have been proposed in recent literature [Debevec et al 2000;Masselus et al 2003;Peers et al 2006]. Precomputed light transport is popular even for synthetic rendering [Sloan et al 2002;Ng et al 2003;Hasan et al 2006]. In essence, these methods directly measure the effects of interreflections under various lighting conditions.…”
Section: Motivationmentioning
confidence: 99%
“…dering for rich lighting effects, such as precomputed radiance transfer using spherical harmonics by Sloan et al [15,16] and all-frequency relighting using wavelets by Ng et al [8,9]. The former allows changing lighting and viewpoint in real-time, but limited to low-frequency illumination.…”
Section: Figmentioning
confidence: 99%